Distributed Control System Design for Portable PC Based CNC Machine - Saputra, Roni Permana; Atmaja, Tinton Dwi; Prawara, Budi (Research Centre for Electrical Power and Mechatronics, Indonesian Istitutes of Sciences, 2014)
The demand on automated machining has been increased and emerges improvement research to achieve many goals such as portability, low cost manufacturability, interoperability, and simplicity in machine usage. These improvements are conducted without ignoring the performance analysis and usability evaluation. This research has designed a distributed control system in purpose to control a portable CNC machine. The design consists of main processing unit, secondary processing unit, motor control, and motor driver. A preliminary simulation has been conducted for performance analysis including linear accuracy and circular accuracy. The results achieved in the simulation provide linear accuracy up to 2 Î¼m with total cost for the whole processing unit is up to 5 million IDR.